Industrial Diversification in American Cities - McLaughlin, Glenn E. (Quarterly Journal of Economics, 1930)
I. Advantages and disadvantages of industrial concentration. — Possible relation to the business cycle, 131. — II. The criterion of concentration and diversification here used: value added by manufacture, 134. — Results for sixteen cities in 1919, 135. — In later years, 138. — III. Relation between industries of producers' goods and of consumers' goods, 146. — Some significant results as to concentration and business fluctuations, 148.